Development Of Smart Pet Monıtorıng System - Mr. Kiran Kumar K, Rishav Pandey, Nirmal Pereira, Dabbara Sai Charan, Anurag Kumar (International Journal of Advanced Science and Technology, 2020)
In this paper, development of a Smart pet care system, which will provide feeding and monitoring assistance of the pet to pet parents who are unable to be present with their pets due to their work/job. The whole project is based on Arduino. ‘Smart Pet Monitoring System’ is designed with components like Arduino, ArduCam, Servo motor, 16*2 LCD, Sensors, ESP8266 Wi-Fi Module, 4x4 membrane keypad and weight sensor, HX711 AD convertor.Arduino is the main component which is used to control all processes. It acts like a controller. A camera is used to monitor the pet, which can be accessed through a dedicated website or a mobile application. A buzzer is used to notify the pet about food dispersal. The purpose of this project is to make monitoring and feeding pet remotely more affordable and efficient. This project also demonstrates the I2C protocol of communication, here used to let multiple Arduino boards communicate with each other.Index Terms: Arduino, Camera, Weight sensor, I2C Protocol, Electric motors